Diachronic study (survey) of terminological units related to hydrotechnical construction in Uzbek, Russian and English languages (Journal of Pedagogical Inventions and Practices, 2022)
The beginning of any new sphere leads to the creation of a certain terminological system, and the development of this industry over the centuries leads to the development of a terminological system.